Pengaruh Aruskas, Likuiditas Dan Profitabilitas Terhadap Return Saham Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Subsektor Makanan Dan Minuman Periode 2017-2021 - Rio Yulian Pradipta; Sunarto Sunarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to investigate and evaluate how cash flow, liquidity, and profitability affect stock returns. The study population consist of food and baverage subsector companies listed on the Indonesian Stock Exchange (IDX) between 2017 and 2021. A sample of 24 companies was created using a targeted sampling technique. Secondary data from numerous reliable sources served as the basis for the data. Cash flow, liquidity, and profitability are independent variables. stock returns is the dependent variable. Secondary data were collcted in this study using a documented approach. According to the test results, profitability has a positive impact on stock returns whereas investment cash flow has no impact and liquidity has a negative impact. Keywords: cash flow, liquidity, profitability, stock return